THE PROBLEM OF TERRORISM AND WAR IN PHILOSOPHY OF J. BAUDRILLARDIN THE SEARCH OF ABSOLUTELY EVIL - Savonova Hanna Ivanovna (World Science, 2019)
The article is aimed at the implementation of the concretization of the concept of "terrorism", the definition of the philosophy of "non-war" based on the moral and ethical values of the consumer society according to the social and philosophical views of Jean Baudrillard; also, on the disclosure of the problem of the search for absolute Evil and its reflection in the historical events of the late XX - early XXI centuries. Originality consists in systematizing the process of myth-symbolizing the terrorist act of September 11, 2001, specifying the role of a terrorist and hostage, clarifying the problem of absolute Evil in the system of values of the consumer society, as well as forming a classification of a new historical type of "non-war" and distinguishing local and hybrid wars, as a kind of «non-war».